Ammoniated salt based solid sorption thermal batteries: A comparative study. (5th June 2021) - Sharma, Rakesh; Anil Kumar, E.; Dutta, Pradip; Srinivasa Murthy, S.; Aristov, Yu.I.; Tokrev, M.M.; Li, T.X.; Wang, R.Z.
Highlights: Ammonia sorption property data for several halide salts are correlated. Ammonia based sorption and resorption thermal batteries are analysed. Thermal batteries for simultaneous heating and cooling are also studied. Thermal performance parameters are compared for different systems. Operating temperature limits are identified for specific ammonia-salt pairs. Abstract: Gas-solid chemisorption pairs of ammonia and halide salts have an edge over other pairs for advanced thermal energy storage batteries due to their abundance, easy availability, cost effectiveness, high sorption capacity, and wide operating temperature range. In the present work, thermodynamic analyses of thermal battery systems are performed for various ammonia-halide salt pairs using measured sorption characteristics. The stored thermal energy can also be upgraded by forming a combination of suitable halide salts. A maximum gravimetric energy storage density of 1664 kJ kg −1 is observed for MnCl2 based thermal battery. The degree of heat upgradation can be as high as 43 °C in case of MnCl2 –CaCl2 based resorption thermal battery. The first law efficiency is observed to be as high as 0.42 for CaCl2 based thermal battery. The decrease in first law efficiency due to parasitic mass is observed to be in the range of 26–37 % and 57–66% for different CaCl2 and MnCl2 thermal batteries, respectively. It is possible to recover the stored thermal energy in the form of simultaneous heating and cooling effects by using specific combination of salts which enhances the overall efficiency. First law efficiency as high as 0.92 can be achieved with a CaCl2 –NaBr resorption thermal battery delivering simultaneous cooling and heating effects at 10 and 55 °C, respectively, while storing thermal energy at 100 °C.